Stable relative equilibria in the system of superconductive and permanent magnetic dipoles - Zub, S.S. (Вопросы атомной науки и техники, 2015)
This paper analytically proves the existence of stable orbital motions in a system of superconductive and permanent magnetic dipoles. As opposed to a system of two permanent magnetic dipoles, that has been studied in the work of I.Tamm and V. Ginzburg in this system we have no <<problem 1/R³>>, because of that the stability of the system becomes possible.